Intercultural education and indigenous peoples in the State of Guerrero, Mexico - Castillo, Ana (2020)
The article maintains that intercultural education emancipates indigenous peoples and contributes to the construction of a dialogical democracy. In addition, he points out that the school plays an important role, since it promotes respect for the Other, fosters more horizontal knowledge and learning among students and teachers. But it also indicates that the lack of budget, the bureaucracy, the discrimination and the rejection of non-western culture impede the construction of a new school. That said, the purpose of this work is to analyze the current situation of indigenous peoples and education in the state of Guerrero. The discussion on this topic allows educational actors and society to reconsider the fact that intercultural dialogue reinforces the sense of belonging and identity of those communities such as the Amuzgos, Mixtecos, Nahuas and Tlapanecos, who have been marginalized. during these last decades. Regarding the methodology, we rely on reflective and interpretive sociology in order to carry out a detailed analysis not only of bibliographic and newspaper sources, but also of the complexities, possibilities and paradoxes of the Mexican educational system.